Memory, Narration, Responsibility. Notes on the Margin of Barbara Skarga’s Identity and Difference - Nowak-Ciesielska, Anna (Sensus Historiae, 2021)
In this article, I am trying to read Barbara Skarga’s reflection on the problems of memory, narration and the ethical dimensions of mnemonic narrative practices, presented in the work Identity and Difference. In the second part of this work, the author deals with the problem of personal identity defined by the concept of self. Many of her considerations are directly related to the issues considered within the theoretical reflection on historical cognition and on broadly understood historical education. I mean such issues as memory, narrative identity, responsibility, evil, conscience, self-autonomy, human integrity. The philosophical reflection of Barbara Skarga illuminates her own experience of life in history and can also be related to our individual and community experiences.